Advances in Stroke Risk Assessment and Cerebrovascular Vessel Wall Imaging. Issue 2 (11th March 2015) - Cunningham, Muriel
As cerebrovascular vessel wall imaging techniques mature, new information will be provided useful for predicting the risk of stroke while increasing diagnostic specificity for a wide variety of common and uncommon intracranial circulatory disorders. Stroke risk prediction models are being revised to incorporate advances in optimized medical therapy and noninvasive imaging.